Drivers of Financial Statement Fraud in IDX-Listed Consumer Goods Firms (2021–2024) - Wardhani, Anak Agung Sagung Paramita Kusuma; Oktapriana, Chita (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2026)
This study examines the effect of external pressure, nature of industry, and financial target on financial statement fraud in consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Grounded in Agency Theory and the Fraud Triangle, this research aims to provide empirical evidence on the dominant drivers of fraudulent financial reporting within emerging markets. Using a quantitative approach with secondary data obtained from annual reports and financial statements, 60 firm-year observations were analyzed. Financial statement fraud was measured using the F-Score, while the independent variables were assessed through established proxy indicators and tested using multiple regression analysis. The findings reveal that external pressure and financial target have a significant positive influence on financial statement fraud, suggesting that high stakeholder expectations and aggressive performance targets increase managerial incentives to manipulate financial information. In contrast, the nature of the industry shows no significant effect, indicating that industry-specific operational characteristics may not contribute substantially to fraud risk within the consumer goods sector. The study contributes theoretically by reinforcing pressure as a key antecedent of fraud and empirically by offering evidence from a post-pandemic Indonesian context. This research provides practical implications for regulators, auditors, and corporate governance actors to enhance fraud risk assessment by focusing on pressure-related indicators. Limitations include its industry-specific scope and reliance on archival data. Future studies are encouraged to explore governance moderating variables and apply mixed-method approaches for deeper insight.